Glial activation in the spinal ventral horn caudal to cervical injury - Windelborn, James A. (2011)
Microglia and astrocytes play complex roles following spinal cord injury (SCI), contributing to inflammatory processes that both exacerbate injury and promote functional recovery by supporting neuro-protection and neuroplasticity. The crossed phrenic phenomenon (CPP) is an example of respiratory plasticity in which C(2) cervical hemisection (C(2)HS) strengthens crossed-spinal synaptic pathways to phrenic motor neurons ipsilateral to injury. We hypothesized that microglia and astrocytes are activated in the phrenic motor nucleus caudal and ipsilateral to C(2)HS, suggesting their potential for involvement in the CPP. To test this hypothesis, an incomplete cervical spinal hemisection (C(2) lateral injury; C(2)LI) was performed, and rats were allowed to recover for 1, 3, 14 or 28 days before collecting perfused spinal tissues. Microglia (via OX42) and astrocytes (via GFAP) were visualized with immunofluorescence microscopy in the C(4)-C(5) ventral horn, the region encompassing most of the phrenic motor nucleus. OX42-occupied fractional area ipsilateral to injury increased with C(2)LI (vs. sham) at 1 (12.5 +/- 1.8%, p<0.001), 3 (29.0 +/- 1.9%, p<0.001), 14 (26.1 +/- 3.1%, p<0.001) and 28 (19.2 +/- 2.0%, p<0.001) days post-C(2)LI. GFAP-occupied fractional area also increased with C(2)LI at 3 (24.4 +/- 3.2%, p<0.001) and 14 (16.8 +/- 8.3%, p=0.012) days, but not at 1 (6.2 +/- 3.9%, p=0.262) or 28 (10.6 +/- 3.9%, p=0.059) days post-C(2)LI. Thus, microglia and astrocytes are activated in the phrenic motor nucleus caudal to C(2)LI, suggesting that they play a role in functional deficits and/or recovery following spinal injury.